Comparison of the effectiveness of radiation protection principles training through multimedia and instructional booklet on the awareness of operating room staff - Raheleh Charmchi; Parisa Moradimajd; Azam Saei; Reza Paydar; Jamileh Abolghasemi (Journal of Education and Health Promotion)
BACKGROUND: Training and awareness regarding radiation protection is crucial for medical staff and operating room personnel to prevent potential hazards from radiation exposure. Various methods are employed to increase the awareness of operating room staff regarding radiation protection principles. This study aimed to evaluate the effectiveness of two training methods, multimedia presentations and instructional booklets, in enhancing the awareness of operating room staff toward radiation protection principles. MATERIALS AND METHODS: In this semi-experimental study, 60 anesthesia and operating room technologists, were purposefully selected and randomly (utilizing an engineering calculator) divided into two intervention groups and one control group. The first group received multimedia-based training, while the second group was provided training through an instructional booklet. Data was collected using a researcher-designed questionnaire before the intervention and again 30 days afterward. Subsequently, the data were analyzed using SPSS version 26, employing analysis of covariance) ANCOVA (and the Bonferroni post hoc test to compare the outcomes among the three groups. RESULTS: No significant difference in mean awareness scores was observed among the three groups before the intervention) P = 0.075(. After the intervention, both multimedia and instructional booklet-based education showed significant improvement in awareness scores compared to the control group) P < 0.001(. Furthermore, the differences between the mean awareness scores of the multimedia-based group and the instructional booklet-based group, as well as the multimedia-based group and the control group, were 26.25 and 40.95, respectively, both statistically significant (P < 0.001). DISCUSSION: The current research findings indicate the effectiveness of both educational methods. However, the multimedia-based education method proved to be more effective in increasing the awareness levels of the study participants compared to the other two groups which is important to increase compliance with standards and implement hospital accreditation criteria to ensure the safety of operating rooms personnel against radiation. Therefore, based on this study’s results, this educational approach is recommended for teaching topics related to radiation protection principles.